Investigation of Rhenium (I) Tri-, Di-, Tetra- Carbonyl Diimine Complexes - Wong, Ngaisum (2023)
Chapter 1 This Chapter provides an introduction to the photophysical and photochemical properties of the complexes of interest in this Thesis highlighting their different excitedstates. A brief background of well-studied rhenium (I) tricarbonyl diimine complex is presented to allow comparison to the much less explored rhenium (I) di- and tetracarbonyl diimine complex which are the subject of this work. A brief outline is given of techniques used within this Thesis namely UV-visible, luminescence and timeresolved infrared (TRIR) spectroscopy. The latter technique is a pump-probe method that has been utilised to investigate the photophysical and photochemical properties of the complexes of interest.